2001
DOI: 10.2304/plat.2001.1.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Peer Interaction and the Learning of Critical Thinking Skills

Abstract: The ability to conduct reasoned argument (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0
9

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(111 citation statements)
references
References 8 publications
(12 reference statements)
4
98
0
9
Order By: Relevance
“…This finding adds to the existing theoretical as well as empirical evidence (e.g. Anderson et al, 2001;Halpern, 2014) that suggests that the acquisition of transferrable CT skills can be achieved mainly through interventions that involve an extended duration and coverage of a large number of courses. Future studies may focus on a more intensive and comprehensive interventions that involve an extended duration and with the inclusion of more than one domain-specific courses.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…This finding adds to the existing theoretical as well as empirical evidence (e.g. Anderson et al, 2001;Halpern, 2014) that suggests that the acquisition of transferrable CT skills can be achieved mainly through interventions that involve an extended duration and coverage of a large number of courses. Future studies may focus on a more intensive and comprehensive interventions that involve an extended duration and with the inclusion of more than one domain-specific courses.…”
Section: Discussionsupporting
confidence: 61%
“…Bensley & Spero, 2014;Dwyer et al, 2012;Solon, 2007), whereas several others reported a non-significant effect (e.g. Anderson, Howe, Soden, Halliday & Low, 2001;McLean & Miller, 2010;Toy & Ok, 2012). Such variability in research outcomes has made it difficult to gain a deeper understanding of the features of Immersion-and Infusion-based interventions for CT. A recent systematic review criticized existing Immersion-and Infusion-based CT intervention studies on the ground that the processes involved in the design and development of the instructional interventions in itself was not sufficiently specified (Tiruneh, Verburgh & Elen, 2014).…”
Section: Teaching Students To Think Critically: Review Of the Empiricmentioning
confidence: 99%
“…The evaluation process that a student must engage with in order to provide feedback is arguably the most important aspect of peer assessment (Ljungman & Silen, 2008;Topping, 2005). This is so because it affords the student the opportunity to practice the skills necessary to evaluate their own work and thus peer-assessment serves to improve skills in selfassessment (Anderson, Howe, Soden, Halliday, & Low, 2001;Topping, 2005).…”
Section: Peer-assessment Reviewmentioning
confidence: 99%
“…In addition, a researcher who forces his research object to think out loud during his activity, will not be able to observe a natural behavioural process. In daily activities, the interaction with other members of the group can be an important mechanism for learning (Anderson & Soden, 2001). Moreover, it is natural for humans to learn or solve something in collaboration with others (Bahrami et al, 2010).…”
Section: Testing In Pairsmentioning
confidence: 99%